THE ROLE OF DEMOCRATIC TRANSITION IN BUILDING GOOD GOVERNANCE - Aissa, Benagoune; Nadia, Salhi (The journal of contemporary issues in business and government, 2024)
This article aims to highlight the role of a democratic systemin the pursuit of good governance, democratic transition is a critical process that lays the foundation for good governance by establishing accountable institutions, fostering citizen participation, and promoting responsive governance essential for stable democracies, Civil society plays a pivotal role in bridging the gap between governments and citizens, advocating for rights, peace building, and enhancing collaboration between stakeholders to achieve good governance.